PERANCANGAN SISTEM PEMILIHAN KETUA BEM (BADAN EKSEKUTIF MAHASISWA) BERBASIS E-VOTING DENGAN METODE CRUD SEBAGAI DIGITALISASI ORGANISASI DI BRI INSTITUTE - Sitorus, Michael; Antonieta DC, Cornelia (Infotech: Journal of Technology Information, 2021)
Entering the digital era and the rapid development of technology, the existence of technology is now increasingly advanced and affordable to make it easier for humans to carry out various activities. Now humans can be helped well in carrying out various activities such as selecting the Chairperson of the Student Executive Board (BEM) using e-voting. The problem in this research is that the election of the head of the BEM still uses a simple information delivery medium, namely in the form of sheets of paper for sending the vision and mission and also for selecting candidates. This of course becomes less than optimal and less efficient, especially in the Covid-19 pandemic situation which requires 98 percent of universities to implement distance learning. The purpose of this research is to create an E-Voting-Based BEM Chair Election system using the PHP programming language and MySql database. The method used is Create, Read, Update, Delete (CRUD). As a result, this system will help universities to realize organizational digitization, especially at BRI Institute as a technology and business-based university.